Tooth Resorption: A Comprehensive Review of Pathophysiology, Classification, Diagnosis and Management - Ponugubati, Charishma Chowdary; Ravi, Ravichandra (Asian Journal of Biological and Life Sciences)
Tooth resorption refers to the loss of dental hard tissues, including dentin, cementum, or bone, due to physiological or pathological processes. Although initially observed in the 16th century, its etiologies, classifications, and treatments have been significantly elucidated in recent years. This review provides a detailed exploration of the biological basis, types, histopathological features, and current clinical management strategies for tooth resorption. Both internal and external forms are examined, with emphasis on diagnostic features and therapeutic approaches. Early recognition and intervention remain pivotal to prevent irreversible damage and tooth loss.
Keywords: Ankylosis; External Resorption; Internal Resorption; Odontoclasts; Orthodontic Resorption; Inflammatory Root Resorption.